Tolvaptan in Pediatric Autosomal Dominant Polycystic Kidney Disease: From Here to Where? - Fei Liu; Chunyue Feng; Huijun Shen; Huaidong Fu; Jianhua Mao (Karger Publishers, 2021)
Background: Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disorder, accounting for approximately 5% of all ESRD cases worldwide. As a vasopressin receptor 2 antagonist, tolvaptan is the FDA-approved therapeutic agent for ADPKD, which is only made available to a limited number of adult patients; however, its efficacy in pediatric patients has not been reported widely. Summary: Tolvaptan was shown to delay ADPKD progression in the Tolvaptan Efficacy and Safety in Management of Autosomal Dominant Polycystic Kidney Disease and Its Outcomes (TEMPO) 3:4 study, Replicating Evidence of Preserved Renal Function: an Investigation of Tolvaptan Safety and Efficacy in ADPKD (REPRISE) trial, and other clinical studies. In addition to its effects on aquaretic adverse events and alanine aminotransferase elevation, the effect of tolvaptan on ADPKD is clear, sustained, and cumulative. While ADPKD is a progressive disease, the early intervention has been shown to be important and beneficial in hypotheses as well as in trials. The use of tolvaptan in pediatric ADPKD involves the following challenges: patient assessment, quality of life assessment, cost-effectiveness, safety, and tolerability. The ongoing, phase 3b, 2-part study (ClinicalTrials.gov identifier: NCT02964273) on the evaluation of tolvaptan in pediatric ADPKD (patients aged 12-17 years) may help obtain some insights. Key Messages: This review focuses on the rationality of tolvaptan use in pediatric patients with ADPKD, the associated challenges, and the suggested therapeutic approaches.